Production and anti-inflammatory and analgesic effects of sphaeralgin from transformed and non-transformed cells in suspension cultures of Sphaeralcea angustifolia (Cav.) G. Don - Reyes-Pérez, Rogelio; Nicasio-Torres, Pilar; González-Cortazar, Manasés; Arellano-Garcia, José de Jesús; Montiel-Ruiz, Rosa Mariana; Vargas-Ruiz, Rodrigo; Pérez-García, Ma. Dolores; Pérez-Hernández, Juanita (Plant cell, tissue and organ culture, 2024)
Sphaeralcea angustifolia is a plant with confirmed anti-inflammatory, immunomodulatory and gastroprotective effects. These properties can be attributed to scopoletin, tomentin, sphaeralcic acid, iso-sphaeralcic acid and 8-methyl-iso-sphaeralcic acid compounds isolated from cells in suspension and hairy root cultures. Genetic transformation with Agrobacterium rhizogenes were used in S. angustifolia cell cultures to increase the production of active secondary metabolites and stimulate the production of other compounds. We observed that non-transformed cells in a suspension of S. angustifolia had a higher growth index after two and three weeks of culture (9.29 and 11.84, respectively) compared with cells in suspension transformed with A. rhizogenes . Both cultures produced sphaeralcic acid, and enhanced production was detected in the transformed cells (0.19 and 0.16 mg/g, respectively). In addition, transformed and non-transformed cells produced a new compound identified as sphaeralgin (dicumarine); a higher yield of sphaeralgin was detected in the transformed cells (2.21 mg/g dry biomass). The anti-inflammatory effects of sphaeralgin in edema models induced with 12-O-tetradecanoylphorbol-13-acetate and ʎ-carrageenan inhibited edema formation in a dose-dependent manner, with a mean effective dose (ED 50 ) of 0.25 mg/ear and 64.56 mg/kg, respectively. During the late phase of the formaline test, sphaeralgin had an antinociceptive effect, with an ED 50 of 1.35 mg/kg.